2018
DOI: 10.15850/amj.v5n4.1496
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Diet, Cosmetics and Degree of Acne Vulgaris in Dermatovenereology Outpatients at Dr. Soetomo General Hospital, Surabaya

Abstract: Background: Acne vulgaris (AV) is a chronic inflammatory multifactorial disease that involves the pilosebaceous unit. The lesions of acne may be either non-inflammatory (comedones, which are blackheads or whiteheads) or inflammatory lesions (papules, nodules or pustules). The effects of diet and cosmetics on acne are still inconclusive. The objective of this study was to analyse the relationship between diet, cosmetics and the degree of AV. Methods: This was a hospital-based, analytic observational study with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
1
0
3
Order By: Relevance
“…ras, diet, stress, kosmetik, suhu, dan obatobatan 3,7. Salah satu faktor penyebab akne vulgaris yaitu penggunaan kosmetik wajah 3.…”
unclassified
“…ras, diet, stress, kosmetik, suhu, dan obatobatan 3,7. Salah satu faktor penyebab akne vulgaris yaitu penggunaan kosmetik wajah 3.…”
unclassified
“…Similar association between acne severity and cosmetics has recently been established in a study from one of the neighboring countries of Pakistan (Shah et al, 2021;Sinha et al, 2016). In another study from Indonesia, it was reported that there exists no significant relationship between acne and cosmetics (Perera et al, 2018;Yueng et al, 2018). In this study, around 29% individuals claimed their acne severity increased by use of cosmetics.…”
Section: Discussionmentioning
confidence: 51%
“…Hal ini sejalan dengan penelitian Yueng 17 di RS Dr. Soetomo Surabaya yang juga menyatakan bahwa tidak ditemukan hubungan bermakna antara penggunaan pelembab dengan tingkat AV. 17 Frekuensi penggunaan krim wajah dapat disesuaikan kondisi kulit dengan tetap memperhatikan kandungan pada krim wajah tersebut agar penggunaan krim tetap aman tanpa menimbulkan risiko masalah kulit seperti jerawat atau memperburuk kondisi jerawat.…”
Section: Bahasanunclassified